Women Resistance in Alice Walker’s: The Color Purple - Samara Nofal Omar (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
The purpose of this study is to analyze the forms of female resistance that appear in the novel The Color Purple and the extent to which the female characters in the novel portray female resistance. It focuses on African-American women’s struggle against exploitation by both the whites and black men. The main purpose of this research is to analyze the tragic experiences of black women in racist societies and their struggles for survival. The female characters have masculine characteristics such as dynamism, boldness, and physical strength. Sophia’s strength, Shug’s sexual confidence, and Harpo’s insecurities are prime examples of the disagreement between the characters’ genders and the traits they portray. The results of this study indicate that female characters show active and passive resistance to various forms of oppression experienced. There endure sexual harassment and physical violence. The resistance of women is explained by the actions of several female characters who finally free themselves from the problems they face. Alice Walker fights against the way black women are being discriminated. Discrimination is on two layers, one being black, another is being female